The temperament of pre-teens at risk of educational and social exclusion - Moanţă, Alina Daniela; Pelin, Florin; Ciolcă, Corina; Nanu, Marian Costin; Mitrache, Georgeta; Badea, Dan; Ciuntea, Lucian Mihai (Frontiers in Psychology, 2023)
Introduction Vulnerability and poverty increase the educational and social exclusion of pre-teens. The goal of the present study was to identify the temperamental characteristics of pre-teens at risk of educational and social exclusion, depending on type of vulnerability and gender. Methods For the study, 329 students (167 boys and 162 girls) at risk of early school leaving were involved and grouped into four categories: preadolescents from single-parent families, students with an absent parent (for example, is working abroad), socially assisted students, and Roma pre-teens (socially assisted). To assess temperament the Early Adolescent Temperament Questionnaire (EATQ-R) was used. Results The results underline that in the case of the four super factors and for the two behavioral scales investigated, the scores (at group level) are, generally, within the average limits. The study highlights the importance of specialists to increase, in the case of pre-teens at risk of early school leaving, Effortful Control, and to decrease Negative Affectivity (which includes frustration and fear) and Depressive Mood. Significant differences between vulnerable boys and girls were observed, in the case of Surgency, Affiliation, and Depressive Mood. Also, using the Mann-Whitney (U) test and an independent sample t-test, gender-dependent differences were highlighted (considering the EATQ-R scales), in the case of each type of vulnerability. Using single-factor multivariate analysis of variances, the differences between preadolescents, depending on the type of vulnerability, were presented. Discussion In the case of Surgency, boys registered significantly higher scores than girls, while in the case of Affiliation and Depressive Mood girls obtained higher values. Gender- and type of vulnerability-dependent differences in temperament were discussed in the case of pre-teens, and showed a temperament-conscious education is necessary in future parental education and teacher training.